A-level accounting - "Wood, Frank" (inancial Times Prentice Hall, Harlow Englan, 2004)
This edition has been restructured to closely match the AQA A-level syllabus. In particular, coverage of partnership accounts is now in one chapter; all company accounting is covered in one chapter; and standard costing and variance analysis is covered in a single chapter.